Formalny i nieformalny status sekretarza polskiego korpusu dyplomatycznego na przykładzie misji w Kopenhadze (1792–1795) - Czekalska, Adrianna (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
When the Great Sejm in 1788 decided to appoint a state foreign service, there was a problem of lack of appropriate officials and right. There were no regulations specific to the work of Polish diplomats posted to foreign royal courts. An example of how imprecise the organizational assumptions of Polish foreign policy resumed in December 1788 is the status of a secretary of the legation, who could act as “charge d’affaires” formal and informal. The article does not exhaust the entire subject matter, but merely mentions some of the problems that the representative with an unregulated diplomatic position had to deal with.